Pengaruh Sarapan terhadap Konsentrasi Belajar - Puteri Sahra Salsabila; Shinta Nareswari (Medula, 2023)
Breakfast is a daily consumption that is considered important to meet nutritional needs. Even though it is considered important, there are still many people who skip breakfast which can have a negative impact on the learning process at school, contribute to obesity, and increase the risk of unhealthy snacks. Breakfast should be done to support learning concentration and meet the nutritional needs needed by the body. Learning is defined as all psychological activities carried out by everyone so that their behaviour is different before and after learning. Attention to learning has been identified as a complex construct in psychology that does not express a unitary concept but involves psychological phenomena that interact with all other cognitive processes. In general, the brain works best when blood glucose levels are in the 80–120 mg/dL range. With the gradual depletion of blood glucose and the consequent energy consumption, people start to feel hungry and tired and experience a decline in cognitive function. A number of studies have reported that eating breakfast decreases cognitive function and work efficiency. Periods of fasting at night, depleting the glucose in the blood. So, in order to maintain its function, the brain needs intake in the morning. As an initial energy supplier, especially as a source of glucose energy for the brain, breakfast is highly recommended for everyone.